Peningkatan Literasi Kosmetik Alami melalui Workshop Green Beauty Lab: Formulasi Masker Wajah Berbasis Bahan Alami pada Siswa SMA - Gunawan, Untung; Kusnaman, Mathias Lourdion; Gracia , Venestrata; Setiawan, Patrycia; Christian, Yulius Evan (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2026)
The use of chemical-based cosmetics without adequate understanding among adolescents is increasing and poses risks of skin irritation and long-term health problems. Education on natural cosmetics is essential to build awareness of choosing safe and environmentally friendly products. This community service activity aimed to improve high school students' knowledge and skills in formulating natural-based facial masks and to foster natural cosmetic literacy. The activity was conducted offline at the FKIK Unika Atma Jaya campus, involving 30 students from grades XI and XII. The method used was an interactive workshop consisting of material delivery on natural cosmetics, hands-on mask formulation practice, and group discussions. Evaluation was conducted using a pre-tes and post-test to measure knowledge improvement, and a Likert-scale questionnaire to assess satisfaction and goal achievement. Data analysis used a Wilcoxon test. There was a significant increase in knowledge after the workshop, with mean scores increasing from 82,67 to 93,33 (p < 0.05). Participants successfully practiced mask formulation, indicating clarity of the material, relevance of the topic, and facilitator skills. The activity was effective in improving natural cosmetic literacy and practical skills among high school students. This program has the potential to be replicated in other schools as an effort to empower the younger generation regarding safe and sustainable natural cosmetics.